2015
DOI: 10.1161/circresaha.116.305406
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin Enhances Cardiac Transplant Rejection

Abstract: Rationale Early graft inflammation enhances both acute and chronic rejection of heart transplants, but it is unclear how this inflammation is initiated. Objective To identify specific inflammatory modulators and determine their underlying molecular mechanisms after cardiac transplantation. Methods and Results We used a murine heterotopic cardiac transplant model to identify inflammatory modulators of early graft inflammation. Unbiased mass spectrometric analysis of cardiac tissue before and up to 72 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In addition to SAA proteins, we found that circulating levels of haptoglobin, another APP that is overexpressed in platelet releasates from cancer mice, reached levels equal to 1 mg mL −1 , and remained elevated when tumor developed. It is noteworthy that, in addition to its antioxidant properties, haptoglobin can regulate the host immune response , with anti‐inflammatory and proinflammatory effects, depending on pathological context . Understanding the contribution of haptoglobin, and other identified APPs, to CAC will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to SAA proteins, we found that circulating levels of haptoglobin, another APP that is overexpressed in platelet releasates from cancer mice, reached levels equal to 1 mg mL −1 , and remained elevated when tumor developed. It is noteworthy that, in addition to its antioxidant properties, haptoglobin can regulate the host immune response , with anti‐inflammatory and proinflammatory effects, depending on pathological context . Understanding the contribution of haptoglobin, and other identified APPs, to CAC will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that haptoglobin exerts its immune effects through increased expression of the proinflammatory cytokines IL-6 and macrophage inflammatory protein-2 (MIP-2), while reducing levels of the antiinflammatory cytokine IL-10. Haptoglobin also enhanced DC graft recruitment and augmented antidonor T cell responses (56). Previous studies using a murine skin transplant model demonstrated that haptoglo-…”
Section: Damps Derived From Extracellular Constituentsmentioning
confidence: 99%
“…Haptoglobin is an acute-phase serum protein that, in addition to binding free hemoglobin, influences free radical formation and angiogenesis. More recently, haptoglobin has been described as a novel mediator of innate immune activation after heart transplantation (55,56). Haptoglobin expression is increased in the context of both human and experimental cardiac transplant rejection, and targeted depletion of haptoglobin led to sustained costimulatory blockade-induced tolerance in an experimental heart transplant model, suggesting that its presence impairs maintenance of tolerance.…”
Section: Damps Derived From Extracellular Constituentsmentioning
confidence: 99%
“…Interestingly, acute phagocytosis and innate inflammation during allograft IRI has been linked to chronic pathophysiology. For example, perioperative and acute inflammation are prognostic for worse long-term transplant outcome ( 201 , 202 ). Graft reperfusion may trigger reperfusion-associated cell death ( 38 ) and cell necrosis occurs during allograft cold storage and continues in allograft reperfusion.…”
Section: Phagocytosis Post Heart Transplantation and New Therapeutic mentioning
confidence: 99%